Spiritualitas Personal Pelayan Dalam Membangun Spiritualitas Jemaat - Aprilia, Ana (Jurnal Lentera Nusantara, 2024)
The background of this study is taken from the urgency of the role of altar servers in the implementation of church worship, especially in GPIBI Persahabatan Solo. Altar servers, as individuals who have the responsibility of leading and directing the liturgy, not only play a technical role, but also a spiritual one. They have a central role in creating a sacred atmosphere that supports the spiritual experience of the congregation during worship. The quality of the altar server's personal spirituality is believed to influence the depth and quality of the congregation's worship, as the altar server serves as a link between the congregation and the ritual elements in the church. In the context of the church, spirituality does not only concern the individual's relationship with God, but also relates to how that spirituality is lived and transmitted in the congregational community. Therefore, altar servers are expected to be spiritual role models who inspire and strengthen the faith of the congregation. Their liturgical responsibilities demand a deep and solid spirituality. This research is based on the assumption that improving the personal spirituality of altar servers has a significant impact on the spirituality of the congregation. Through a qualitative approach, this study aims to examine the spiritual experiences of altar servers and their contribution in strengthening the congregation's spiritual relationship with God. A deeper understanding of the spiritual role of altar servers is expected to contribute to the church in developing the spirituality of servers, so as to support the spiritual needs of the congregation more effectively.AbstrakLatar belakang penelitian ini diambil dari urgensi peran pelayan altar dalam pelaksanaan ibadah gereja, khususnya di GPIBI Persahabatan Solo. Pelayan altar, sebagai individu yang memiliki tanggung jawab dalam memimpin dan mengarahkan liturgi, tidak hanya berperan secara teknis, tetapi juga secara spiritual. Mereka memiliki peran sentral dalam menciptakan suasana sakral yang mendukung pengalaman spiritual jemaat selama ibadah. Kualitas spiritualitas pribadi pelayan altar diyakini berpengaruh terhadap kedalaman dan kualitas ibadah jemaat, karena pelayan altar berfungsi sebagai penghubung antara jemaat dan elemen-elemen ritual dalam gereja. Dalam konteks gereja, spiritualitas tidak hanya menyangkut hubungan individu dengan Tuhan, tetapi juga berkaitan dengan bagaimana spiritualitas tersebut dihidupi dan ditransmisikan dalam komunitas jemaat. Oleh sebab itu, pelayan altar diharapkan mampu menjadi teladan rohani yang menginspirasi dan memperkuat iman jemaat. Tanggung jawab liturgis yang mereka emban menuntut adanya spiritualitas yang mendalam dan kokoh.Penelitian ini didasarkan pada asumsi bahwa peningkatan spiritualitas personal para pelayan altar memiliki dampak signifikan terhadap spiritualitas jemaat. Melalui pendekatan kualitatif, penelitian ini bertujuan untuk mengkaji pengalaman spiritual pelayan altar serta kontribusi mereka dalam memperkuat hubungan rohani jemaat dengan Tuhan. Pemahaman yang lebih mendalam mengenai peran spiritual pelayan altar diharapkan dapat memberikan kontribusi bagi gereja dalam mengembangkan spiritualitas pelayan, sehingga mampu mendukung kebutuhan rohani jemaat secara lebih efektif.